Eksplorasi Kualitatif Implementasi Sistem Pendukung Keputusan Perekrutan Karyawan Menggunakan Metode Moora: Studi Berbasis Systematic Literature Review - Salwa Robbul Izzah; Hanifatun Nisa; Nurul Firdaus; Fatakhul Widjoyo; Riyan Sisiawan Putra (Jurnal Ilmu Manajemen dan Pendidikan | E-ISSN : 3062-7788, 2025)
This research aims to explore the application of a decision support system (DSS) using the MOORA method in the context of employee recruitment. Using a descriptive qualitative approach and the Systematic Literature Review (SLR) method, the focus of this research was to understand more about the experience of the users, their perceptions of fairness in the selection process, as well as the impact of the system implementation on decision-making. To achieve this objective, semi-structured interviews were conducted with key users of the to explore MOORA's effectiveness in reducing subjectivity and improving efficiency. The findings showed that the system succeeded in improving transparency and accuracy in the selection process, although there are still technical challenges and a need for adaptation technical challenges and the need for user adaptation were initial barriers.